Recepcija romanov The Adventures of Tom Sawyer in Adventures of Huckleberry Finn v Sloveniji - Trupej, Janko (Vestnik za tuje jezike, 2019)
The article addresses the Slovenian reception of the novels The Adventures of Tom Sawyer and Ad-ventures of Huckleberry Finn - two classic literary works that have been translated into Slovenian more than once. The analysis, based on reader response theory, encompassed approximately one thousand issues of Slovenian serial publications (including academic print), and shed light on the extent to which the Slovenian reception differed from that in the original culture. Since the analysis is divided into the period between the two world wars, the socialist period and the period after Slovenia gained independence, it illuminates how the reception changed over time. Considering the socio-political circumstances during a particular period makes it possible to reach conclusions about why writing about both literary works sometimes changed considerably even within a few years. In the interwar period, no clear ideological influences are evident, while during the socialist period there are frequent condemnations of racism, capitalism, organized religion and other aspects of American society. This is most characteristic of the reviews that were published in the first few years after World War II; then, after relations between the United States and Yugoslavia improved significantly, this was reflected in the reception of the novels in question. In the period after Slovenia declared independence, both novels were again primarily considered to be juvenile literature, and most articles about them do not have an ideological agenda.
Keywords: ameriška književnost; ameriška proza; ameriški romani; literarna recepcija; Slovenija; Twain, Mark